Analysis of glycerol and dihydroxyacetone metabolism in Enterococcus faecium. Issue 8 (17th April 2021) - Staerck, Cindy; Wasselin, Valentin; Budin-Verneuil, Aurélie; Rincé, Isabelle; Cacaci, Margherita; Weigel, Markus; Giraud, Caroline; Hain, Torsten; Hartke, Axel; Riboulet-Bisson, Eliette
ABSTRACT: Glycerol (Gly) can be dissimilated by two pathways in bacteria. Either this sugar alcohol is first oxidized to dihydroxyacetone (DHA) and then phosphorylated or it is first phosphorylated to glycerol-3-phosphate (GlyP) followed by oxidation. Oxidation of GlyP can be achieved by NAD-dependent dehydrogenases or by a GlyP oxidase. In both cases, dihydroxyacetone phosphate is the product. Genomic analysis showed that Enterococcus faecium harbors numerous genes annotated to encode activities for the two pathways. However, our physiological analyses of growth on glycerol showed that dissimilation is limited to aerobic conditions and that despite the presence of genes encoding presumed GlyP dehydrogenases, the GlyP oxidase is essential in this process. Although E. faecium contains an operon encoding the phosphotransfer protein DhaM and DHA kinase, which are required for DHA phosphorylation, it is unable to grow on DHA. This operon is highly expressed in stationary phase but its physiological role remains unknown. Finally, data obtained from sequencing of a transposon mutant bank of E. faecium grown on BHI revealed that the GlyP dehydrogenases and a major intrinsic family protein have important but hitherto unknown physiological functions. Abstract : Glycerol catabolism is restricted to the oxygen-dependent glycerol kinase/oxidase pathway but the role of the dihydroxyacetone kinase pathway remains unknown in E. faecium .